A de novo heterozygous missense BSCL2 variant in 2 siblings with intractable developmental and epileptic encephalopathy. (October 2019) - Fernández-Marmiesse, Ana; Sánchez-Iglesias, Sofía; Darling, Alejandra; O'Callaghan, María M.; Tonda, Raúl; Jou, Cristina; Araújo-Vilar, David
Highlights: Seipin, encoded by BSCL2 gene, is involved in brain function. Several BSCL2 variants are related with different neurological diseases. Some BSCL2 variants can lead to a severe neurodegenerative disorders. A new de novo BSCL2 variant (c.566 T > A) is related to an epileptic encephalopathy. Abstract: Purpose: We present the case of 2 siblings with profound refractory epilepsy and neurological regression that began at the ages of 3 and 6 months. Diagnosis remained elusive despite extensive metabolic and genetic workups, including use of a targeted next-generation sequencing panel for epilepsy genes. Methods: Whole-exome sequencing was performed for the 2 siblings and their unaffected parents, in addition to fibroblast cell culture, RNA extraction and reverse-transcription, and cDNA PCR. Brain tissue from one of the siblings was collected post-mortem for neuropathological examination, including histology and immunohistochemistry. Results: A de novo nucleotide change (c.566 T > A; p.(Met189Lys)) in exon 4 of the BSCL2 gene was detected in the 2 siblings, and confirmed by Sanger sequencing. This variant was absent in the parents and in a third, unaffected sibling. Conclusion: Given the de novo nature of the variant, its absence from public and in-house databases, our in silico pathogenicity predictions, and co-segregation of the variant with the disease phenotype, we believe that this novel variant is associated with the epileptic encephalopathy phenotype of the 2 siblings. Our findings provide the first evidence of an association between a heterozygous BSCL2 variant and developmental and early infantile epileptic encephalopathy. Further functional studies will be needed to elucidate the pathophysiological mechanisms underlying this new BSCL2 -associated phenotype.